Migration and plugging laws of plugging-selection balls in fine profile control process of layered waterflooding wells - Yan An; Fushen Ren; Xiaolong Liu; Jinzhao Hu; Tiancheng Fang; Baojin Wang; Min Luo (Scientific Reports)
Abstract The ball-pitching plugging-selection profile control technology represents an effective and low-cost means of adjusting the profile of waterflooding well. The technology primarily utilizes polymer balls to plug the perforations, thereby achieving the effect of fine profile control. This paper aims to elucidate the migration and plugging laws of plugging-selection balls in wellbore and perforation plugging processes. Accordingly, the effects of flow rate of waterflooding, and density, diameter, quantity of plugging-selection balls on the plugging effect of perforation were investigated through numerical simulation and experiments. This revealed the movement laws of waterflooding and plugging-selection balls during ball-pitching process. The findings of the research indicated that the diversion effect mainly was primarily observed in the layers with strong water absorption capacity, and the migration process of plugging-selection balls demonstrated both single and multiple plugging effects, which were influenced by the parameters of waterflooding and plugging-selection balls. The well plugging effect could be achieved when the flow rate of waterflooding was 2 m3/h, the density of ball and waterflooding was similar, the plugging-selection ball diameter was 10 mm, and the ball-perforation number ratio exceeded 1.0. The application of typical wells indicated that, the ball-pitching plugging-selection profile control technology could enhance oil production, finely control reservoir utilization, and enhance economic benefits.